Tissue-Specific Functions of fem-2/PP2c Phosphatase and fhod-1/formin During Caenorhabditis elegans Embryonic Morphogenesis. Issue 7 (1st July 2018) - Refai, Osama; Smit, Ryan B; Votra, SarahBeth; Pruyne, David; Mains, Paul E
Abstract: The cytoskeleton is the basic machinery that drives many morphogenetic events. Elongation of the C. elegans embryo from a spheroid into a long, thin larva initially results from actomyosin contractility, mainly in the lateral epidermal seam cells, while the corresponding dorsal and ventral epidermal cells play a more passive role. This is followed by a later elongation phase involving muscle contraction. Early elongation is mediated by parallel genetic pathways involving LET-502 /Rho kinase and MEL-11 /MYPT myosin phosphatase in one pathway and FEM-2 /PP2c phosphatase and PAK-1 /p21 activated kinase in another. While the LET-502 /MEL-11 pathway appears to act primarily in the lateral epidermis, here we show that FEM-2 can mediate early elongation when expressed in the dorsal and ventral epidermis. We also investigated the early elongation function of FHOD-1, a member of the formin family of actin nucleators and bundlers. Previous work showed that FHOD-1 acts in the LET-502 /MEL-11 branch of the early elongation pathway as well as in muscle for sarcomere organization. Consistent with this, we found that lateral epidermal cell-specific expression of FHOD-1 is sufficient for elongation, and FHOD-1 effects on elongation appear to be independent of its role in muscle. Also, we found that fhod-1 encodes long and short isoforms that differ in the presence of a predicted coiled-coil domain. Based on tissue-specific expression constructions and an isoform-specific CRISPR allele, the two FHOD-1 isoforms show partially specialized epidermal or muscle function. Although fhod-1 shows only impenetrant elongation phenotypes, we were unable to detect redundancy with other C. elegans formin genes.